Gender differences in prescribing patterns for patients with Parkinson’s disease in Japan: a retrospective observational study using insurance claims databases - Seki, Morinobu; Kawata, Yayoi; Hayashi, Ayako; Fujimoto, Shinji (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease (PD) is a neurodegenerative disorder, with increasing prevalence among aging populations. Gender differences in PD extend to symptom presentation and treatment response, suggesting the need for gender-specific management strategies.MethodsThis gender-stratified analysis of a retrospective observational study used data from three nationwide Japanese healthcare databases. Patients aged ≥30 years diagnosed with PD between June 2016 and May 2021 were included. Patient demographics, prescribing patterns, and levodopa dosages were analyzed descriptively.ResultsOf 39,731 patients with PD identified, females (n = 22,724) outnumbered males (n = 17,007), especially in the ≥75 years group. Levodopa was the most commonly prescribed drug for both genders. The mean ± standard deviation maximum levodopa dose was numerically higher in males (520.0 ± 426.8 mg) compared with females (498.7 ± 424.2 mg). Usage of monoamine oxidase B inhibitors (MAOBI) was 24.0% in males and 18.9% in females. Among newly treated patients, >70% of both genders started treatment with levodopa monotherapy; a slightly higher proportion of males tended toward levodopa combination therapy. For both genders, concomitant drugs were most commonly MAOBI, non-ergot dopamine agonist, and zonisamide. However, females tended to receive a more diverse range of medications than these three drugs.ConclusionThis analysis highlights the high number of elderly female patients with PD in Japan. Slight gender differences in maximum levodopa dose and prescriptions for anti-PD drugs were observed. These findings emphasize the importance of personalized treatment approaches in PD management considering gender-specific differences in drug efficacy and side effects.Clinical trials registrationhttps://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000053425, identifier UMIN000046823.